Comportamiento estático de un pilar de circona sometido a envejecimiento artificial. Método de elementos finitos (2015)
ABSTRACT: Some studies on the effect of zirconia aging mention a degree of reduction of zirconia’s fracture strength varying from 20 to 40%, while other authors argue that aging does not affect the material’s strength. The aim of this study was to evaluate the response of a zirconia abutment subjected to static loads and artificial aging using the finite element method (FEM). Methods: modeling of the Tapered Screw- Vent implant and the zirconia Zimmer® abutment (Zimmer Dental1 900 Aston Avenue Carlsbad, CA 92008-7308 USA). Four models were designed: one with an implant of 3.7 mm in diameter and a 3.5 mm diameter abutment, another with an implant of 4.7 mm in diameter and a 4.5 mm diameter abutment, and other two with the same dimensions but changing the final fracture limit to 40%, analyzing the response of different components to specific loads. Results: models subjected to decreases in zirconia abutment fracture strength did not show zirconia ifferences in terms of von Mises values. A factor of safety allowed observing the working threshold of the zirconia abutment; failure occurred at values lower than 1. Conclusion: by modifying zirconia’s properties in order to simulate aging, the factor of safety decreases at values lower than 1. However, the applied forces under which the safety factor decreases are higher than normal masticatory forces.